Multifractal analysis of slacken surface in hydrocarbon molecules through fuel additives - G. Arockia Prabakar; R. Uthayakumar; S. Abdul Azis (Egyptian Journal of Petroleum)
This paper investigates the effect of organic fuel additives (Bio-Glycerol) on fuel savings, emission reduction and extend engine life. Using this enzyme, a motor cycle is tested five times. The test report shows the reduction in the release of carbon monoxide (CO) and hydrocarbon upto 60%. The use of organic fuel additives in diesel vehicles for different periods of time reveals the reduction in air pollution by 55%. Finally, we have experimented scanning electron microscope (SEM) test for organic fuel additives with biodiesel. The SEM image shows the existence of molecules of hydrocarbons. The analysis elucidated the complex morphology of molecules of hydrocarbons in fuel additives with biodiesel. The hydrocarbon molecules are slackened and irregular as it refers to the fractal form. SEM Photograph images are analyzed by multifractal analysis. MFA (multifractal analysis) is carried out according to the method of moments, i.e., the probability distribution is estimated for moments which differ from -150<q<150 and the generalized dimensions are estimated from the log/log slope of the probability distribution for the respective moments over box sizes. Generalized dimensions D(q) are attained for this box size range, which are capable of characterizing heterogeneous spatial slackened surface.